"The importance of community and the necessity of the numinous": how chapel contributes to UK private senior schools. - Macpherson, Anthony (2024)
Many private senior schools have a Christian foundation and a purpose-built chapel, alongside a regular requirement for the whole school community to worship together. The focus of this study is on the contribution that chapel - both as place and practice - makes to these school communities. The research aimed to establish new knowledge that provides valuable insights for the sector about the potential benefits of maintaining the practice of chapel. The findings of this thesis are underpinned by Durkheim’s sociological account of religion as the symbolic expression of social experience, and further supported by a broad range of research literature that considers the possible contribution of religion and communal worship to people’s lives. A multiple case-study design was developed to investigate chapel in three private senior schools. 40 participants were interviewed using qualitative, semi-structured, and in-depth interviews. These generated a rich dataset, analysis of which produced accounts of chapel’s contribution in each school. The multiple case approach aimed to ensure a greater range of voices and a richer narrative account, and it was also hoped that some ‘analytic generalisability’ might be possible from cross-case analysis. Participants were selected according to their role or position in each school community and care was taken to include the key stakeholders including the head, chaplain, director of music, director of admissions and marketing, houseparents, current parents, alumni, and current pupils. Against a backdrop of declining Christian adherence within the UK, and utilising Durkheim’s sociological account of religion as a means of enhancing community cohesion (by distinguishing between that which is ‘profane’ and that which is ‘sacred’), this study highlights the socio-cultural features of chapel on one hand and its sacred features on the other. This distinction is captured by the summary of chapel’s contribution offered by one participating head, which eventually became the title for this thesis: “the importance of community and the necessity of the numinous”. Under the first main theme, ‘building community, culture, and identity’, four important sub-themes were identified and explored. Following Durkheim, ‘community cohesion and identity’ was the most prominent sub-theme expressed by participants, and almost all of them described this as a core benefit of whole-school chapel. ‘Moral messages and values education’ was identified as another strong sub-theme describing chapel’s distinctive contributions; many participants considered chapel a particularly conducive environment for moral guidance. A third dimension of chapel was ‘communal singing’ which was reported to be an important and enjoyable feature of chapel for many, especially the pupils. The culture of communal singing was not strong in all schools, but participants nevertheless referenced its benefits as a potentially uplifting and community-enhancing activity. ‘School marketing and promotion’ was a less prominent theme in the analysis, and in most cases, references were to how chapel plays a very limited role in this aspect of school life. The second main theme arising from the analysis I term ‘engaging with the sacred, and taking pupils beyond their everyday and profane experiences’. This too had several important sub-themes. ‘Engagement with faith and religion’ was described as a key contribution of chapel by almost all participants, regardless of their personal faith background; it was seen as valuable for pupils to have the opportunity to encounter, and question matters of faith, enabling them to reach a more informed viewpoint. ‘Opportunity for calm reflection’ was highlighted by most participants, with chapel often described as the only time and place during the busy week that allowed for genuine space and separation from the demands of everyday school life. A third sub-theme was ‘comfort and reassurance’ and seemed to be particularly important where schools had experienced recent tragedy or loss. Chapel was considered a uniquely important space in these cases for both communal and private expressions of grief. The central contributions of chapel discussed in this thesis were referenced by a large majority of participants, seemingly irrespective of their personal faith position, their position in the school, or which case-study school they were connected to. Unsurprisingly, not all participants were positive about chapel, and some were particularly opposed to its compulsory status. However, the overwhelming majority spoke favourably about chapel and expressed support for its continued, whole-school practice, referencing the sacred setting of chapel in positive terms. In general, chapel’s religious content and Christian teaching were attributed far less importance than chapel’s affordances to 1) gather as a school community, and 2) to spend time in recognition and appreciation of the non-material aspects of human life.